Progress in psoriasis therapy via novel drug delivery systems - Nitha Vincent; Ramya Devi D; Vedha Hari BN (PAGEPress Publications, 2014)
Psoriasis is a lifelong condition which is caused by the negative signals produced by immune system, which leads to hyper proliferation and other inflammatory reactions on the skin. In this case, keratinocytes which are the outermost layer of skin possess shortened life cycle and results in the alteration of desquamation process where the cytokines will come out through lesions of affected patients and as a result, scaling marks appears on the skin. These conditions may negatively affect the patient's quality of life and lead to psychosocial stress. Psoriasis can be categorized as mild, moderate and severe conditions. Mild psoriasis leads to the formation of rashes, and when it becomes moderate, the skin turns into scaly. In severe conditions, red patches may be present on skin surface and becomes itchy. Topical therapy continues to be one of the pillars for psoriasis management. Drug molecules with target effect on the skin tissues and other inflammations should be selected for the treatment of psoriasis. Most of the existing drugs lead to systemic intoxication and dryness when applied in higher dose. Different scientific approaches for topical delivery are being explored by researches including emollient, modified gelling system, transdermal delivery, spray, nanogels, hydrogels, micro/nano emulsion, liposomes, nano capsules etc. These topical dosage forms are evaluated for various physico chemical properties such as drug content, viscosity, pH, extrudability, spreadability, toxicity, irritancy, permeability and drug release mechanism. This review paper focus attention to the impact of these formulation approaches on various anti-psoriasis drugs for their successful treatment.